2021
DOI: 10.3390/agronomy11040645
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Analysis of Diversity in DH Lines and Hybrids of Winter Oilseed Rape (Brassica napus L.)

Abstract: Limited genetic variability is a major problem in rapeseed breeding, whose strict selection, limited geographical range and a short period of domestication has led to a reduction in genetic and phenotypic diversity. Assessing specific populations for the greatest genetic diversity for many traits simultaneously, requires the evaluation of multi-feature characteristics. The aim of this study was to estimate the variability of DH (doubled haploid) lines and two generations of winter oilseed rape hybrids. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…For studied phenotypic traits, we identified in total 354 significant associations, of which 168 in year 2015 and 186 in 2016, and only 36 of them were common in both years. Differences in the associations probably resulted from the influence of the environment on the observed features, which is also reflected in their variability [39]. There are few published studies about the association of SSR markers with phenotypic traits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For studied phenotypic traits, we identified in total 354 significant associations, of which 168 in year 2015 and 186 in 2016, and only 36 of them were common in both years. Differences in the associations probably resulted from the influence of the environment on the observed features, which is also reflected in their variability [39]. There are few published studies about the association of SSR markers with phenotypic traits.…”
Section: Discussionmentioning
confidence: 99%
“…The following quantitative traits were evaluated: beginning of flowering (days), length of flowering (days), plant height (cm), the number of branches per plant, the number of siliques per plant, silique length (mm), the number of seeds per silique, and thousand seed weight (g). Phenotypic evaluation of measured agronomic traits and their variation was described in detail by Łopaty ńska et al [39].…”
Section: Plant Materialsmentioning
confidence: 99%
“…We have applied multivariate statistical analysis such as CVA in our studies. This type of analysis was applied in studies of Lopatynska et al [34] to detect differences in DH lines and hybrids of winter rapeseed e.g., in thousand seed weight and the first two canonical variates together explained from 66.12% to 82.03% of the total variation depending on the year, since in our experiment, CVA explained 44.14% of the entire variation.…”
Section: Discussionmentioning
confidence: 99%
“…If the parental form did not significantly differ from each other, there is a possibility to obtain from which possesses a heterosis effect. Such studies were conducted by Lopatynska et al [34] in winter rape and helped to choose the valuable genotypes for breeding programs. In our studies, we have found significant heterosis effect for CF parameters (Fv/Fm, Area, PI and ETo/CS), as well as for yield elements (TGW, GNP) and biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, understanding the genetic structure and mode of inheritance for target traits is crucial for improving hybrid or openpollinated varieties of oilseed rape. Additive gene effects indicate the efficiency of selection, while non-additive effects, such as dominance and overdominance, contribute to hybrid variety development (Amiri Oghan et al, 2018;Łopatyńska et al, 2021;Masood et al, 2019).…”
Section: Introductionmentioning
confidence: 99%